Article Review: Media Representations of Hamas in Conflict Reportin - Siti Noor Fazelah Mohd Noor; Azizi Basar (Journal of Humanistic, Management and Social Science Review, 2024)
This paper examines the representation of Hamas in media reporting through a Critical Discourse Analysis (CDA) perspective, focusing on the terminological choices employed by various news outlets and their impact on public perception. By analyzing coverage from selected news outlets, the study reveals how terms like "militant group," "terrorist," and "Palestinian fighters" reflect underlying ideological and political beliefs. The findings highlight the significant role of media ownership and political context in shaping news narratives. Employing Martin and White’s Appraisal System and Van Leeuwen’s Social Actors Representation Theory, the study details how language and social actor representations influence public perceptions. The paper concludes that understanding these discursive strategies is essential for fostering a nuanced and informed public understanding of the conflict, emphasizing the need for balanced reporting practices to maintain journalistic integrity and mitigate the broader implications of biased media coverage.